PENGARUH DEBT TO EQUITY RATIO DAN CURRENT RATIO TERHADAP RETURN ON ASSETS PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Indra Saputra; Rusmanto Rusmanto; Mega Andani (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, This purpose of this study was to found whether effect Debt to Equity Ratio (DER) and Current Ratio (CR) on the Return On Assets (ROA) within Otomotif company which registered in Indonesia Stock Echange Period 2012-2016. The research method used is a quantitative method by collecting data and then reprocessing it with the 16.00 version of the SPSS program. The sample drawn by purposive sampling and fulfill sample selection criterion. The results of this study show partially the Debt to Equity Ratio variable has an effect on Return on Assets, while the Current Ratio variable does not affect Return on Assets. Simultaneously shows that the variable Debt to Equity Ratio and Current Ratio affect Return on Assets.